ANALISIS MODEL PEMBELAJARAN KONVENSIONAL DAN MODEL PEMBELAJARAN ISLAM - Huda, Samsul; Rusdiono; Rusydi, Lina Najwatur (Primer Edukasi Journal, 2026)
This study aims to determine the comparison between conventional learning models and Islamic learning models. This research is a qualitative study employing library research methods, with data collection conducted through documentation. Data analysis utilizes a comparative technique, specifically analyzing the philosophical foundations of both conventional and Islamic learning and dissecting these concepts through the perspective of Islamic education. The results indicate that Islamic education possesses a comprehensive repertoire of learning models designed to develop students' independence guided by virtuous life values. This approach aims to form individuals with noble character and righteousness across their intellect, emotions, and actions. The study finds that these two learning models differ significantly in concept; therefore, creative collaboration is required from teachers acting as mediators, facilitators, and catalysts in the learning process. By integrating these models based on specific conditions and situations, an innovative and creative synergy between conventional and Islamic learning can be achieved. Ultimately, this collaborative model is highly implementable and meets the needs of comprehensive education in the modern era. Keywords: Education, Islam, Learning, Model